DEVELOPMENT OF SALARY CARDS IN THE SYSTEM OF CASHLESS PAYMENTS IN CONDITIONS OF FINANCIAL INSTABILITY ON THE EXAMPLE OF SBERBANK OF RUSSIA - K. V. Ekimova; S. S. Galasova; V. V. Manuylenko (Вестник университета)
The need to develop Bank salary cards in the system of non-cash payments in the conditions of financial instability caused by the Covid-19 pandemic has been substantiated in the study. For the formation of a new view on the application of the Bank payroll cards economic substance “of the modern Bank salary card” based on technologies of contactless payments has been expanded, the advantages of using salary cards for banks and clients – legal entities and individuals have been defined, the best experience of Sberbank of Russia on the use of Bank salary cards from the point of view of its extrapolation to regional banks, taking into account their specifics has been studied. As a result, the main directions for the development of salary projects have been proposed, including the definition of incentive provisions for their application, ensuring security, confidence in salary projects and contactless payment, regulating the risk of occurrence of accounts payable and accounts receivable between business entities, the need to modernize individual banking service, formation of innovative salary cards.